The significance of cysteine synthesis for acclimation to high light conditions - Speiser, Anna; Haberland, Stefan; Watanabe, Mutsumi; Wirtz, Markus; Dietz, Karl-Josef; Saito, Kazuki; Hell, Rüdiger (Frontiers in Plant Science, 2015)
Situations of excess light intensity are known to result in the emergence of reactive oxygen species that originate from the electron transport chain in chloroplasts. The redox state of glutathione and its biosynthesis contribute importantly to the plant’s response to this stress. In this study we analysed the significance of cysteine synthesis for long-term acclimation to high light conditions in Arabidopsis thaliana. Emphasis was put on the rate-limiting step of cysteine synthesis, the formation of the precursor O-acetylserine (OAS) that is catalysed by serine acetyltransferase (SERAT). Wild type Arabidopsis plants responded to the high light condition (800 μmol m-2 s-1 for 10 days) with synthesis of photo-protective anthocyanins, induction of total SERAT activity and elevated glutathione levels when compared to the control condition (100 μmol m-2 s-1). The role of cysteine synthesis in chloroplasts was probed in mutant plants lacking the chloroplast isoform SERAT2;1 (serat2;1) and two knock-out alleles of CYP20-3, a positive interactor of SERAT in the chloroplast. Acclimation to high light resulted in a smaller growth enhancement than wild type in the serat2;1 and cyp20-3 mutants, less induction of total SERAT activity and OAS levels but similar cysteine and glutathione concentrations. Expression analysis revealed no increase in mRNA of the chloroplast SERAT2;1 encoding SERAT2;1 gene but up to 4.4-fold elevated SERAT2;2 mRNA levels for the mitochondrial SERAT isoform. Thus, lack of chloroplast SERAT2;1 activity or its activation by CYP20-3 prevents the full growth response to high light conditions, but the enhanced demand for glutathione is likely mediated by synthesis of OAS in the mitochondria. In conclusion, cysteine synthesis in the chloroplast is important for performance but is dispensable for survival under long-term exposure to high light and can be partially complemented by cysteine synthesis in mitochondria.